Synthesis of glycoconjugates utilizing the regioselectivity of a lytic polysaccharide monooxygenase - Westereng, Bjørge; Kračun, Stjepan K.; Leivers, Shaun; Arntzen, Magnus Ø.; Aachmann, Finn L.; Eijsink, Vincent G. H. (Scientific reports, 2020)
Polysaccharides from plant biomass are the most abundant renewable chemicals on Earth and can potentially be converted to a wide variety of useful glycoconjugates. Potential applications of glycoconjugates include therapeutics and drug delivery, vaccine development and as fine chemicals. While anomeric hydroxyl groups of carbohydrates are amenable to a variety of useful chemical modifications, selective cross-coupling to non-reducing ends has remained challenging. Several lytic polysaccharide monooxygenases (LPMOs), powerful enzymes known for their application in cellulose degradation, specifically oxidize non-reducing ends, introducing carbonyl groups that can be utilized for chemical coupling. This study provides a simple and highly specific approach to produce oxime-based glycoconjugates from LPMO-functionalized oligosaccharides. The products are evaluated by HPLC, mass spectrometry and NMR. Furthermore, we demonstrate potential biodegradability of these glycoconjugates using selective enzymes.